Diagnostic and therapeutic conduct in neurological injuries: (cervical cord injuries) - Benedek, Pedro (Cirugía del Uruguay, 1974)
Cervical cord wounds are infrequent and are cassed by section, compression, contusion and commotion. In this paper the pathological anatomy of spine and bone lesions are studied. Wounds caused by high-speed bullets stand out far their importance. There is a clinical analysis of complete and incomplete spine section, spinal shock_ and compression and wounds in roots and plexus. Rules are set for first aid, transportationa and diagnosis of these patients. Adequate position and transportation are of prime importance. Al! spinal cord wounds should be explored as early as possible in arder to establish indications and opportunity. Posterior approach by laminectomy is preferred by author. Main basic ta-ctics are described. Case material consisting of 4 recent patients is included.